Section 2: Patient Records: Electronic Patient Records and their Benefit for Patient Care - Knaup, P.; Managing Editor for the IMIA-Yearbook Section on Patient Records (Yearbook of Medical Informatics, 2006)
To summarize current excellent research in the field of patient records.Synopsis of the articles selected for the IMIA Yearbook 2006.Current research in the field of patient records analyses users’ needs and attitudes as well as the potential and limitations of electronic patient record systems. Particular topics are the questions physicians have when assessing patients during ward rounds, the timeliness of results when ordered electronically, the quality of documenting haemophilia home therapy, attitudes towards patient access to health records and adequate strategies for record linkage in dependence on the intended purpose.The best paper selection of articles on patient records shows examples of excellent research on methods used for the management of patient records and for processing their content as well as assessing the potential, limitations of and user attitudes towards electronic patient record systems. Computerized patient records are mature, so that they can contribute to high quality patient care and efficient patient management.
Keywords: Medical Informatics; International Medical Informatics Association; Yearbook; medical records; computerized medical records systems